If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 5x + 3 + 9 = 8x + 4 + 3x Reorder the terms: 3 + 9 + 7x + 5x = 8x + 4 + 3x Combine like terms: 3 + 9 = 12 12 + 7x + 5x = 8x + 4 + 3x Combine like terms: 7x + 5x = 12x 12 + 12x = 8x + 4 + 3x Reorder the terms: 12 + 12x = 4 + 8x + 3x Combine like terms: 8x + 3x = 11x 12 + 12x = 4 + 11x Solving 12 + 12x = 4 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 12 + 12x + -11x = 4 + 11x + -11x Combine like terms: 12x + -11x = 1x 12 + 1x = 4 + 11x + -11x Combine like terms: 11x + -11x = 0 12 + 1x = 4 + 0 12 + 1x = 4 Add '-12' to each side of the equation. 12 + -12 + 1x = 4 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = 4 + -12 1x = 4 + -12 Combine like terms: 4 + -12 = -8 1x = -8 Divide each side by '1'. x = -8 Simplifying x = -8
| 2(s*1.6)-5(2-s)=1.9 | | yx=zx | | 4x^2-9x-1=0 | | 25s^2+60s=-36 | | 95=8c-3c+15 | | 3x+29=12x-52 | | p-1.34=12.8 | | Y=9y-56 | | 39.03+X=3.5X+X | | 85x+2=p+90 | | 3x-2=9x-4 | | 3x+60=7x+12 | | 7h+15=48 | | 39.05+X=3.4X+X | | 3x+6=2x+4 | | y-2=10 | | 5.5q-2.2-5.1q=-0.6q-3.4 | | 2(x+1)=3x-2 | | 2a+4(2a+2)=48 | | 5y+5=6y | | -2p+4=5p-10 | | 3-2x=4x+15 | | 5x=3x^2-1 | | 6(x+1)=2x-1 | | 3-2x=4x+14 | | .16d+.6=.25(d-2) | | 9y+3-5y=7+3y+8 | | 2.05X=20+X | | 9y+3-5y=7 | | 5z-5=-2z+19 | | 9z+5-5z=6+3z+9 | | 14x+9-3=13x-3 |